2019
DOI: 10.1038/s41467-019-12419-8
|View full text |Cite
|
Sign up to set email alerts
|

A Chlamydia pneumoniae adhesin induces phosphatidylserine exposure on host cells

Abstract: In mammalian cells, the internal and external leaflets of the plasma membrane (PM) possess different phospholipids. Phosphatidylserine (PS) is normally confined to the inner (cytoplasmic) membrane leaflet. Here we report that the adhesin CPn0473 of the human pathogenic bacterium Chlamydia pneumoniae (Cpn) binds to the PM of human cells and induces PS externalization but unexpectedly not apoptosis. PS externalization is increased in human cells exposed to infectious Cpn cells expressing increased CPn0473 and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It has been shown that C. pneumoniae can prevent the occurrence of host cell apoptosis; therefore, we investigated whether Ax treatment affected host cell death during C. pneumoniae infection. According to Galle et al, the assessment of apoptosis in C. pneumoniae -infected cells via annexin V staining is not accurate due to the C. pneumoniae -induced externalization of phosphatidylserine on the host cell membrane, which provides a binding site for annexin V and creates a false-positive apoptosis signal [ 30 ]. Therefore, we determined caspase 3/7 activity using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that C. pneumoniae can prevent the occurrence of host cell apoptosis; therefore, we investigated whether Ax treatment affected host cell death during C. pneumoniae infection. According to Galle et al, the assessment of apoptosis in C. pneumoniae -infected cells via annexin V staining is not accurate due to the C. pneumoniae -induced externalization of phosphatidylserine on the host cell membrane, which provides a binding site for annexin V and creates a false-positive apoptosis signal [ 30 ]. Therefore, we determined caspase 3/7 activity using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest either a potential T3 secretion, which we could not verify thus far, or that the cluster proteins are important part of the chlamydial surface and/or the cOMC (chlamydial outer membrane complex). Other proteins localizing to the cOMC like Momp or the adhesins OmcB, LipP, or the Pmps are highly immunogenic (Su et al, 1990;Moelleken and Hegemann, 2008;Moelleken et al, 2010;Galle et al, 2019). However, none of the Mbp cluster proteins was found in a genome-wide approach identifying immunogenic Cpn surface proteins (Montigiani et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of ANX5 staining for detection of apoptosis in Chlamydia- infected cells is also questionable, because Chlamydia infection itself can induce phosphatidylserine externalization in the absence of an activation of the apoptotic program (Galle et al . 2019 ). Moreover, DNA ladders induced by C. trachomatis L2 were atypical and it was therefore proposed that the mechanism of DNA fragmentation in infected cells was different from that that operates during apoptosis (Ying et al .…”
Section: Pro-death Activities Of Chlamydiaementioning
confidence: 99%